Exploring motivational patterns in high-performing pianists: evidence from Cliburn competitors’ biographies - Chen, Xiao (Frontiers in Psychology, 2024)
This research examines the motivational patterns of high-performing classical pianists, characterized by a combination of implicit motives (i.e., non-conscious preferences for specific incentives). Utilizing the Linguistic Inquiry and Word Count (LIWC) software, I analyzed textual data from biographies of 107 pianists (i.e., Juniors aged 13 to 17: n = 38; Professionals aged 18 to 30: n = 30; Amateurs aged 35 and older: n = 39) participating in the prestigious 2022-2023 Van Cliburn Competitions. My results showed distinct profiles of implicit motives among pianists compared to non-pianists, with significantly higher need for achievement and need for power. While professional pianists exhibited the lowest level of need for power, junior pianists demonstrated the highest level of need for affiliation. Gender and age predicted part of pianists’ implicit motives. Male pianists demonstrated higher need for achievement than females. Finally, age negatively predicted need for affiliation. These findings highlight the motivational patterns within the classical piano community, offering theoretical implications for understanding implicit motives and practical applications for pianist education. Study limitations and future research directions are discussed.